Evaluation of Interethnic Differences in Repinotan Pharmacokinetics by Using Population Approach - Tanigawa, Takahiko; Heinig, Roland; Kuroki, Yoshihiro; Higuchi, Shun (DRUG METABOLISM AND PHARMACOKINETICS, 2006)
Repinotan is a selective full serotonin receptor agonist at the 5-HT1A subtype which has been studied in phase I and II studies involving over 500 healthy subjects and patients. Repinotan is primarily metabolized by CYP2D6 which is known to be subject to polymorphism and ethnic differences in its quantitative and qualitative expression pattern. In order to investigate the effect of ethnicity on repinotan pharmacokinetics (PK) between a Caucasian and Japanese population and to explain PK variability, this population PK evaluation was conducted. A population PK model was established based on the data of 1314 blood samples from 241 patients from 3 Phase II studies. This analysis has characterized the repinotan PK, with particular attention to ethnicity. Using the MIXTURE subroutine of NONMEM, evidence was provided for different CL groups. Repinotan plasma levels in the ‘High CL’ subgroup, which comprised the majority of patients, did not show relevant differences between a Japanese and Caucasian population. In the ‘Low CL’ subgroup, Japanese and Caucasian populations were different. These findings are consistent with the published literature, which reports ethnic differences in the distribution of CYP2D6 activity. The finding of a greater percentage of patients with intermediate CL in the Japanese population falling between poor and extensive metabolizers is consistent with the distribution pattern of CYP2D6 in the Japanese population. The results of this evaluation can be used to assist in designing future trials.